2010
DOI: 10.1016/j.apcatb.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and catalytic activity of CuFeZSM-5 catalysts for oxidative degradation of Rhodamine 6G in aqueous solutions

Abstract: This study presents an evaluation of the catalytic performances of Fe and Cu containing ZSM-5 zeolites for oxidation of Rhodamine 6G. Fe and Cu were loaded by ion exchange or through hydrothermal synthesis. The catalytic process was carried out in an aqueous solution using H2O2 as an oxidant. The catalyst prepared by hydrothermal synthesis showed the highest activity (100% decolorization, 59.1% aromatic degradation and 51.8% TOC removal at initial pH of 3.5). This catalyst was stable against leaching even at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…An important observation here revealed that at solution original pH of 6.1, the complete degradation of CMP was obtained within 15 min of reaction. The activity of nZVI in the neutral pH range is higher than that of many reported heterogeneous Fenton-like catalysts [4,10,12,38,39]. Thus, no or less pH adjustment of the medium is needed for effective oxidation over the wider pH range, which is an important advantage for application.…”
Section: Effect Of Phmentioning
confidence: 80%
“…An important observation here revealed that at solution original pH of 6.1, the complete degradation of CMP was obtained within 15 min of reaction. The activity of nZVI in the neutral pH range is higher than that of many reported heterogeneous Fenton-like catalysts [4,10,12,38,39]. Thus, no or less pH adjustment of the medium is needed for effective oxidation over the wider pH range, which is an important advantage for application.…”
Section: Effect Of Phmentioning
confidence: 80%
“…The precise procedures for preparation and characterization of the catalysts were described in Ref. [24]. Metal contents and Si/Fe ratios of the catalysts were determined by ICP-AES method.…”
Section: Catalystsmentioning
confidence: 99%
“…The reason for this may be that copper and cerium species cover the external surface of ZSM-5, blocking a number of zeolite channels, and impeding entry of N 2 into the pores. XRD patterns ( No diffraction peaks attributed to either copper or cerium oxides are observed, which suggests that the copper and cerium species are well dispersed on the ZSM-5 support [15,16].…”
Section: Structure and Morphologymentioning
confidence: 99%